2012
DOI: 10.1152/japplphysiol.01362.2011
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10reverses mitochondrial dysfunction in atorvastatin-treated mice and increases exercise endurance

Abstract: Statins are cholesterol-lowering drugs widely used in the prevention of cardiovascular diseases; however, they are associated with various types of myopathies. Statins inhibit 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase and thus decrease biosynthesis of low-density lipoprotein cholesterol and may also reduce ubiquinones, essential coenzymes of a mitochondrial electron transport chain, which contain isoprenoid residues, synthesized through an HMG-CoA reductase-dependent pathway. Therefore, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 34 publications
3
53
2
1
Order By: Relevance
“…We already know that CoQ 10 participates in the electron transport chain in mitochondria (27) and that statins can interfere with CoQ 10 , compromising cellular energy production (28). La Guardia et al (29) have demonstrated that simvastatin inhibits mitochondrial respiration, depletes CoQ 10 , and increases hydrogen peroxide production.…”
Section: Discussionmentioning
confidence: 99%
“…We already know that CoQ 10 participates in the electron transport chain in mitochondria (27) and that statins can interfere with CoQ 10 , compromising cellular energy production (28). La Guardia et al (29) have demonstrated that simvastatin inhibits mitochondrial respiration, depletes CoQ 10 , and increases hydrogen peroxide production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some 20,21 but not all studies [22][23][24] suggest that improvements in cardiorespiratory fitness in response to exercise training may be blunted by statin therapy. Therefore, in the current study we sought to assess the impact of cardiorespiratory fitness on the incidence of type 2 diabetes in dyslipidemic patients treated with statins.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Peak exercise capacity (Metabolic Equivalents) was estimated by use of standardized equations. 20,21 One…”
Section: Assessments Of Exercise Capacitymentioning
confidence: 99%
“…The same finding was presented subsequently by the authors when they analyzed statin use in hypertensive patients [42]. However, statins not only induce muscle pain in humans, reducing physical activity participation and consequently affecting exercise performance, but also as growing evidence indicates in both human and animal models, they may directly compromise aerobic exercise capacity and training adaptations [25,43,44]. Along these lines, Kokkinos and Myers [39] delineated in a recent review that exercise intensity shows a strong association with cardiovascular disease risk; therefore, the reduction in the highest tolerable exercise intensity while taking statins should also be a concern for both clinicians and patients.…”
Section: Introductionmentioning
confidence: 53%